Design and prototype development of problem solving game (Adik Bijak Pecahan) - Mahmud, Rosnaini; Abdullah, Yusri; Ab. Jalil, Habibah; Mohd Daud, Shaffe (UTM Academic Leadership (UTMLead), Universiti Teknologi Malaysia, 2016)
Over the years, student showed a poor performance in mathematic problem solving. It is proven that student belief and traditional teaching and learning of mathematics which focusing into routine problem solving significantly plays a role in problem solving. Teachers put more efforts into procedural knowledge that leads to the memorization of formula and procedures with little efforts on understanding the mathematical concepts. This case limits the student ability to explore and investigate the essence of the problems and produce various problem solving strategies. Recent studies identified computer game could be used as an interactive and meaningful problem solving experience. However, there is an issue on how to integrate pedagogy and instructional design with a computer design. Therefore, this study proposes a Computer Game Instructional Design Model (CG-ID) to assist the design and development of problem solving game (Adik Bijak Pecahan).